Brain Repair - Bähr, Mathias (Advances in Experimental Medicine and Biology, 2006)
Brain Repair, addresses all relevant issues underlying the mechanisms of brain damage, brain plasticity and post-traumatic reorganisation after CNS lesions. This book is divided the three major sections that follow; cellular and molecular basis of brain repair, plasticity and reorganisation of neural networks, and experimental therapy strategies. Brain Repair is written by high profile, international experts who describe in detail the newest results from basic research and highlight new model systems, techniques and therapy approaches. Based on a careful analysis of the cellular and molecular reaction patterns of the CNS to lesions, the contributions cover possibilities for endogenous reorganisation and repair as well as exciting new therapies emerging from basic research, some of which have already been introduced into the clinics. Thus, this book is unique in bridging the gap between basic and clinical research. It will be a valuable tool for all students, researchers and clinicians interested in understanding the brain's capacity to cope with lesions and interested in learning about emerging new therapy concepts.